Precision management of pollination services to blueberry crops - Cavigliasso, Pablo; Negri, Pedro; Viel, Matias; Graziani, Milagros María; Challiol, C.; Bello, Fernando; Saez, Agustin (Nature, 2022)
While the cultivated area of pollinator-dependent crops is increasing, pollinator availability is decreasing, leading to problems in many agroecosystems. For this reason, pollinator-dependent crop growers often rent beehives to support their pollination requirements to sustain fruit productivity. However, the efficiency of those pollination systems has not been extensively studied. Here, we compared the effect of “precision” pollination (i.e., application of pesticides coordinated with growers, audit of hives, dietary supplementation and individual distribution of hives) with conventional practices (i.e., pesticides applications without coordination with growers and no audit of hives, low maintenance of hives and hives distributed in large groups) on the mean level of pollination and fruit production and quality in blueberry crops. In nine blueberry fields, we measured bee visitation rate to flowers, fruit set, fruit firmness and fruit weight. On average, precision-pollinated plots had 70% more bee visits to flowers and produced 13% more fruits that were 12% heavier and 12% firmer than those obtained through conventional practices. These results showed that pollination efficiency could be improved if key management related to bee strength, distribution and health care are taken into account. Due to these results, we encourage growers and beekeepers to include precision pollination practices to both increase the productivity of blueberry fields and the wellbeing of honey bees within agroecosystems.